2009
DOI: 10.3340/jkns.2009.45.6.336
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Hemifacial Spasm after Microvascular Decompression

Abstract: Objective : The factors that influence the prognosis of patients with hemifacial spasm (HFS) treated by microvascular decompression (MVD) have not been definitely established. We report a prospective study evaluating the prognostic factors in patients undergoing MVD for HFS. Methods : From January 2004 to September 2006, the authors prospectively studied a series of 293 patients who underwent MVD for HFS. We prospectively analyzed a number of variables in order to evaluate the predictive value of independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 23 publications
5
21
1
Order By: Relevance
“…[8,9,17] But none was previously found to be significantly different between immediate cure and delayed cure groups. [5,6] In this extensive investigation, multivariate analysis revealed a significant correlation between preoperative anticonvulsant therapy and delayed cure after MVD.…”
Section: Preoperative Anticonvulsant Therapy As a Predictive Factor Fmentioning
confidence: 86%
See 2 more Smart Citations
“…[8,9,17] But none was previously found to be significantly different between immediate cure and delayed cure groups. [5,6] In this extensive investigation, multivariate analysis revealed a significant correlation between preoperative anticonvulsant therapy and delayed cure after MVD.…”
Section: Preoperative Anticonvulsant Therapy As a Predictive Factor Fmentioning
confidence: 86%
“…[8] Although some papers showed limited improvement with a high complication rate for preoperative MVD, [1,10] recent surgical results of late reoperation didn't show significant differences from those undergoing their initial MVDs. [16,21] Our results showed that cumulative spasm free rate at 3 months after operation was 97%.…”
Section: Assessment Of Persistent Spasm After Mvdmentioning
confidence: 99%
See 1 more Smart Citation
“…First, immediate spasm after MVD was the predictor for the unsuccessful surgical outcome in both the younger and elderly group. Immediate spasm after MVD was not assessed as a predictor for surgical outcome in previous studies, and only spasm at 3 months after MVD was evaluated as a risk factor and associated with a long-term outcome in our previous study [26]. Additionally, in our study, severe indentation grade reduced the risk of unsuccessful outcome in the younger group.…”
Section: Discussionmentioning
confidence: 46%
“…Only a few studies utilized clinical data as prognostic factors of surgical outcome and complications, but often with diverse results [23,26]. We assessed the risk factors for the unsuccessful outcome and complications using multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%